(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bio-medical waste is constantly a source of worry owing to the risk it possess to the community’s health. COVID-19 is an extremely infectious in nature and deadly virus. A huge amount of biomedical waste is produced to fight against such situations. Traditional waste management solutions cannot cope with covid waste since the rate of waste creation is quite high and infectious. Safety equipment like PPE kits, testing kits, and other medical waste is generated while the handling of COVID-19 patients. The long survival of the corona virus on diverse surfaces is a significant source of its spread. Such infectious waste has become a major environmental and social issue that must be handled. This work provides light on several aspects of the COVID-19 waste volume status and issues associated with COVID-19 waste management. Better waste management can decrease environmental exposure time, transportation danger, and so on. Some recommendations like a small local COVID-19 waste treatment plant may help in reducing the danger of corona virus transmission and mobility, as well as limiting its risks of the hazardous component.